2014
DOI: 10.1186/1471-2261-14-78
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of using an electronic nicotine-delivery device (electronic cigarette) on myocardial function: comparison with the effects of regular cigarettes

Abstract: BackgroundElectronic cigarettes have been developed and marketed in recent years as smoking substitutes. However, no studies have evaluated their effects on the cardiovascular system. The purpose of this study was to examine the immediate effects of electronic cigarette use on left ventricular (LV) function, compared to the well-documented acute adverse effects of smoking.MethodsEchocardiographic examinations were performed in 36 healthy heavy smokers (SM, age 36 ± 5 years) before and after smoking 1 cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 32 publications
3
122
1
12
Order By: Relevance
“…Furthermore, some of these studies were contradictory, with some reporting no cardiovascular harm,11, 12 whereas others found e‐cigarettes to be harmful 13, 14. In support of the latter notion, several studies have shown that e‐cigarettes are associated with an increase in blood pressure, aortic stiffness, endothelial dysfunction, and oxidative stress 6, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some of these studies were contradictory, with some reporting no cardiovascular harm,11, 12 whereas others found e‐cigarettes to be harmful 13, 14. In support of the latter notion, several studies have shown that e‐cigarettes are associated with an increase in blood pressure, aortic stiffness, endothelial dysfunction, and oxidative stress 6, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 13 articles met inclusion criteria for this review [49][50][51][52][53][54][55][56][57][58][59][60][61]. One article reported on the clinical outcomes of interest (two cases of MI) [49].…”
Section: Research Question #2mentioning
confidence: 99%
“…One article reported on the clinical outcomes of interest (two cases of MI) [49]. Eleven articles measured heart rate and BP after EC exposure [50][51][52][53][54][55][56][57][58][59][60]. In 5 of these articles, investigators followed participants for at least 1 week [49,[57][58][59][60], but in 7 articles, authors only reported acute outcomes (changes over b 5 h of exposure) [50][51][52][53][54][55][56].…”
Section: Research Question #2mentioning
confidence: 99%
See 2 more Smart Citations